2016
DOI: 10.1111/cdev.12575
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: An Asian Americanist Perspective on Child Development

Abstract: In this commentary, we put forth an Asian Americanist perspective on child development that frames, expands upon, and at times challenges the contextual, conceptual, and methodological ideas put forward by Kiang et al., Mistry et al., and Yoshikawa et al. (this volume). This Asian Americanist perspective draws upon scholarship in Asian American Studies and critical race theory to bridge the historical, conceptual, and methodological contributions of the three articles. We also aim to challenge current and futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…MPTP is a by-product in the synthesis of 1-methyl-4-phenyl-4-propionoxypiperidine (MPPP) (Ziering and Lee, 1947). MPTP itself is not toxic, but after entering the brain, it is converted into toxic 1-methyl-4-phenylpyridiniumion (MPP + ) under the action of monoamine oxidase B. MPP + is specifically transported to dopaminergic neurons of the SN by DA transporter and then induces the occurrence of PD by inhibiting mitochondrial complex I (Langston et al, 1984;Chiba et al, 1984;Castagnoli et al, 1985;Lee et al, 2011). Our results demonstrated that apoferritin can prevent MPTP-induced weight loss and improve motor deficits.…”
Section: Ll Open Access Isciencementioning
confidence: 99%
“…MPTP is a by-product in the synthesis of 1-methyl-4-phenyl-4-propionoxypiperidine (MPPP) (Ziering and Lee, 1947). MPTP itself is not toxic, but after entering the brain, it is converted into toxic 1-methyl-4-phenylpyridiniumion (MPP + ) under the action of monoamine oxidase B. MPP + is specifically transported to dopaminergic neurons of the SN by DA transporter and then induces the occurrence of PD by inhibiting mitochondrial complex I (Langston et al, 1984;Chiba et al, 1984;Castagnoli et al, 1985;Lee et al, 2011). Our results demonstrated that apoferritin can prevent MPTP-induced weight loss and improve motor deficits.…”
Section: Ll Open Access Isciencementioning
confidence: 99%
“…This framework deepens our understanding of the experiences of Asian American emerging adults within the context of a racially charged society, and the impact of incidences that are directly experienced and/or witnessed has on one’s racial and ethnic identity. AsianCrit posits that top-down study designs that rely solely on quantitative measures are, by themselves, not able to account for the heterogeneity of Asian American experiences (Lee et al, 2016). We have selected a qualitative method for this study in order to capture in-depth, detailed personal accounts that can illuminate the diversity of Asian American voices and experiences.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The atmosphere acts as a selective window to electromagnetic waves, transmitting most of the visible sunlight and blocking harmful ultraviolet and X-rays 1 . Recently, the transparency window in the long-wavelength infrared, which ranges from 8 to 13 μm, has received great attention because it allows for below-ambient cooling without energy consumption [2][3][4][5][6][7][8][9][10][11][12][13][14][15] . The principle…”
Section: Manuscriptmentioning
confidence: 99%